Post-mortem findings in Spanish patients with COVID-19; a special focus on superinfections - Ruiz-Cáceres, Inmaculada; Hermida Romero, Teresa; Guerra Merino, Isabel; Portu Zapirain, Joseba; Pérez-Mies, Belén; Sánchez-Conde, Matilde; Riaño, Marina Alonso; Rubio, Rafael; Fortés Alen, Jose; Vidal González, Ánxela; Salas Antón, Clara; Múñez, Elena; et al. (Frontiers in Medicine, 2023)
Whole-body autopsies may be crucial to understand coronavirus disease 2019 (COVID-19) pathophysiology. We aimed to analyze pathological findings in a large series of full-body autopsies, with a special focus on superinfections. This was a prospective multicenter study that included 70 COVID-19 autopsies performed between April 2020 and February 2021. Epidemiological, clinical and pathological information was collected using a standardized case report form. Median (IQR) age was 70 (range 63.75–74.25) years and 76% of cases were males. Most patients (90%,) had at least one comorbidity prior to COVID-19 diagnosis, with vascular risk factors being the most frequent. Infectious complications were developed by 65.71% of the patients during their follow-up. Mechanical ventilation was required in most patients (75.71%) and was mainly invasive. In multivariate analyses, length of hospital stay and invasive mechanical ventilation were significantly associated with infections (p = 0.036 and p = 0.013, respectively). Necropsy findings revealed diffuse alveolar damage in the lungs, left ventricular hypertrophy in the heart, liver steatosis and pre-infection arteriosclerosis in the heart and kidneys. Our study confirms the main necropsy histopathological findings attributed to COVID-19 in a large patient series, while underlining the importance of both comorbid conditions and superinfections in the pathology.